Meeting the challenges of millennium development goals: practice in an Indian district - Raju, M. Naga (2003)
This paper describes the initiatives taken by a District Collector to achieve the Millennium Development Goals (MDGs) in the Sourth Tripura District, through the various existing development programmes, implemented by the Government. The paper states that while many Government programmes are geared intrinsically towards achievement of the MDGs: there is still a need to orient these activities towards involving local self government bodies and civil society groups. This is in order to focus these programmes towards achievement of MDGs and to ensure better delivery of intended outputs. The various strategies adopted for this purpose in South Tripura are described thereafter. The efforts made in the area of poverty alleviation, primary education, health, environment and gender mainstreaming are covered in detail. - Reproduced.
Keywords: Public administration